Control of silicification by genetically engineered fusion proteins: Silk–silica binding peptides. (15th March 2015) - Zhou, Shun; Huang, Wenwen; Belton, David J.; Simmons, Leo O.; Perry, Carole C.; Wang, Xiaoqin; Kaplan, David L.
Graphical abstract: Abstract: In the present study, an artificial spider silk gene, 6mer, derived from the consensus sequence of Nephila clavipes dragline silk gene, was fused with different silica-binding peptides (SiBPs), A1, A3 and R5, to study the impact of the fusion protein sequence chemistry on silica formation and the ability to generate a silk–silica composite in two different bioinspired silicification systems: solution–solution and solution–solid. Condensed silica nanoscale particles (600–800 nm) were formed in the presence of the recombinant silk and chimeras, which were smaller than those formed by 15mer-SiBP chimeras [1], revealing that the molecular weight of the silk domain correlated to the sizes of the condensed silica particles in the solution system. In addition, the chimeras (6mer-A1/A3/R5) produced smaller condensed silica particles than the control (6mer), revealing that the silica particle size formed in the solution system is controlled by the size of protein assemblies in solution. In the solution–solid interface system, silicification reactions were performed on the surface of films fabricated from the recombinant silk proteins and chimeras and then treated to induce β-sheet formation. A higher density of condensed silica formed on the films containing the lowest β-sheet content while the films with the highest β-sheet content precipitated the lowest density of silica, revealing an inverse correlation between the β-sheet secondary structure and the silica content formed on the films. Intriguingly, the 6mer-A3 showed the highest rate of silica condensation but the lowest density of silica deposition on the films, compared with 6mer-A1 and -R5, revealing antagonistic crosstalk between the silk and the SiBP domains in terms of protein assembly. These findings offer a path forward in the tailoring of biopolymer–silica composites for biomaterial related needs.